Climate, displacement and mental health. Overlapping challenges and opportunities - Campbell, Raramai; Ramos, Cristina; Takaindisa, Joyce; Maviza, Gracsious (2025)
Climate change and forced displacement are deeply interconnected crises with profound mental health consequences. More than 120 million people are forcibly displaced worldwide, with the majority living in climate-vulnerable countries. This brief examines how the interaction between climate change, displacement, and mental health generates compounding risks that traditional humanitarian and climate responses are ill-equipped to address. Based on a review of the literature and field research in the Tongogara Refugee Settlement (Zimbabwe), this brief highlights how climate hazards such as extreme heat, floods, and droughts exacerbate trauma, disrupt livelihoods, and weaken social support systems. Climate-related stressors intensify pre-existing psychological distress and limit displaced populations’ capacity for adaptation. Yet, communities also display remarkable resilience through social networks, and grassroots climate action initiatives. The brief proposes seven strategies to build integrated responses that recognize displaced populations as active agents of resilience: embedding mental health in climate adaptation programs, improving climate risk communication, developing inclusive early warning systems, promoting peer-support networks, addressing gendered vulnerabilities, and adopting long-term climate-resilient planning in displacement settings.